THE BEHAVIOUR OF STRESS PATTERN ON ENGLISH WORDS ENDING IN -IC - Sukrisno, Alim (Language Circle: Journal of Language and Literature, 2010)
ABSTRACTThis study was carried out to observe the word stress pattern on English words ending in Ã¢â‚¬â€œIC.Ã‚Â  It was aimed at confirming a phenomenon that there is a regular stress pattern on the group of English words aboveÃ¢â‚¬â€that is the majority of those words always receive a primary stress on the penultimate syllable of the words. The background why this sort of stress pattern is worth studying is that the patterns ofÃ‚Â  stress on English words are very much arbitrary so that it is quite difficult to pronounce English words with proper stress pattern. Whereas, mistakes in assigning stress on English words may cause differences in meanings which are not desiredÃ‚Â  by the speaker. The type of method used in this study is inventory and descriptive. The findings of this research indicate that out of 2388 words inventorized from Macquarie Dictionary,Ã‚Â  2361 (99%) of English words ending in Ã¢â‚¬â€œIC must be stressed on the penultimate syllable, while only 27 (0.01%) of this type of words displays a deviating stress pattern. The result of this research is quite useful for: firstly, learners of English who want to have a good degree of English pronunciation, and secondly,Ã‚Â  teachers of English in guiding their students to be able to give proper and accurate stress on English words in general and English words ending in Ã¢â‚¬â€œIC in particular. To prove whether or not students as well teachers of English, especially students of English in English Departments, have made use of the result of this research in their pronunciation, it is suggested that a research on pronunciation be conducted. Ã‚Â Key words: stress, penultimate, syllable